Exposure in vitro to an Environmentally Isolated Strain TC09 of Cladosporium sphaerospermum Triggers Plant Growth Promotion, Early Flowering, and Fruit Yield Increase - Li, Zhijian T.; Janisiewicz, Wojciech J.; Liu, Zongrang; Callahan, Ann M.; Evans, Breyn E.; Jurick, Wayne M.; Dardick, Chris (Frontiers in Plant Science, 2019)
A growing number of bacteria and fungi have been found to produce volatile organic compounds (VOCs) that can promote plant growth. Here we report the identification of an environmentally isolated strain of Cladosporium sphaerospermum (herein named TC09), that substantially enhances plant growth via VOCs beyond what has previously been reported. When cultured on Murashige and Skoog (MS) medium under in vitro conditions, tobacco seedlings (Nicotiana tabacum) exposed to TC09 cultures for 20 days increased stem height and whole plant biomass up to 25- and 15-fold, respectively, over controls without exposure. TC09-mediated growth promotion required >5 g/L sucrose in the plant culture medium and was influenced by the duration of exposure ranging from one to ten days, beyond which no differences were detected. When transplanted to soil under greenhouse conditions, TC09-exposed tobacco plants retained higher rates of growth. Comparative transcriptome analyses using tobacco seedlings exposed to TC09 for 10 days uncovered differentially expressed genes (DEGs) associated with diverse biological processes including cell expansion and cell cycle, photosynthesis, phytohormone homeostasis and defense responses. To test the potential efficacy of TC09-mediated growth promotion on agricultural productivity, pepper plants (Capsicum annuum L.) of two different varieties, Cayenne and Minisweet, were pre-exposed to TC09 and planted in the greenhouse to monitor growth, flowering, and fruit production. Results showed that treated pepper plants flowered 20 days earlier and yielded up to 213% more fruit than untreated controls. Altogether the data suggest that exposure of young plants to C. sphaerospermum produced VOCs may provide a useful tool to improve crop productivity.